2020
DOI: 10.1038/s41598-020-63302-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of mCRPC management in patients treated with radium-223

Abstract: Bone is the most common site of metastasis in metastatic castration-resistant prostate cancer (mCRPC), which is associated with pain and skeletal events. Radium-223 dichloride (Xofigo) is an alphaemitting radioactive isotope that can specifically target bone lesions. Herein, we report the results of a retrospective analysis that documents our experience in the use of radium-223. Data from 63 patients (pts) with mCRPC who underwent radium-223 treatment from December 2015 to September 2017 were collected. Radium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Of note, we found that all PET-responders presented a significant reduction in PSA/ ALP levels with respect to the baseline values, with a good correlation, although not statistically significant, between ∆TLA and ∆PSA. It has to be underlined that several reports indicate that PSA dosage might not represent a reliable approach for monitoring the response to treatment, since it may present a transitory increase after the first cycle of 223 Ra-therapy, in relation to the so-called "PSA flare" due to the release of PSA from tumor cell lysis [21]. The correlation between ∆TLA and ∆PSA found in our cohort might be explained by the inclusion criteria we applied for the enrollment, since only patients who had completed three cycles of 223 Ra-therapy were considered, thus minimizing the interference of "PSA flare" occurring in the first month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we found that all PET-responders presented a significant reduction in PSA/ ALP levels with respect to the baseline values, with a good correlation, although not statistically significant, between ∆TLA and ∆PSA. It has to be underlined that several reports indicate that PSA dosage might not represent a reliable approach for monitoring the response to treatment, since it may present a transitory increase after the first cycle of 223 Ra-therapy, in relation to the so-called "PSA flare" due to the release of PSA from tumor cell lysis [21]. The correlation between ∆TLA and ∆PSA found in our cohort might be explained by the inclusion criteria we applied for the enrollment, since only patients who had completed three cycles of 223 Ra-therapy were considered, thus minimizing the interference of "PSA flare" occurring in the first month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment sequence involves taxane chemotherapeutics (docetaxel and cabazitaxel) and novel androgen deprivation therapy (abiraterone acetate, enzalutamide, apalutamide and darolutamide). Sipuleucel-T, an immune-modulatory cellular therapy, is only approved in the US, and treatment with Radium-223 for bone metastases has been moved to the third line of treatment due to a restriction of use by the EMA, although it is of benefit for particular patients [ 33 , 34 ]. First-line treatment of mCRPC is usually performed with abiraterone acetate and prednisone, enzalutamide, docetaxel or cabazitaxel.…”
Section: Castration Resistancementioning
confidence: 99%
“…A number of recently published real-world studies have described large series of patients treated with 223 Ra: they confirmed that the use of 223 Ra in therapeutic sequencing of mCRPC patients is active regardless of the treatment line, in which it was administered. [20][21][22][23] In particular, Rizzini et al 21 the changes occurring during its administration. The data concerning the changes in PSA and alkaline phosphatase levels during 223 Ra administration are very useful for assessing the clinical benefit of the treatment.…”
mentioning
confidence: 99%